Langerhans cell and non Langerhans cell histiocytosis: so different? - Gelmetti, C. (European Journal of Pediatric Dermatology, 2007)
The Author reports the clinical and laboratory criteria that do not support the strict distinction between Langerhans cell and non Langerhans cell histiocytosis as reported in the relevant literature.